Bandizip: an approach to lossless compression of database files - Marcillo, Fabricio (2025)
Data compression is an essential process in computer science and information theory to reduce the size of information through specialized techniques that eliminate statistical or structural redundancies. This process can be lossless, maintaining data integrity, or lossy, sacrificing accuracy for greater compression. Applications of data compression range from optimizing storage to improving data transfer performance, albeit at a computational cost that must be balanced. Choosing the right compression format can significantly impact the performance of database and storage operations. Notable formats include ZIP, ZIPX, 7Z and XZ, each with unique characteristics that make them more appropriate for certain contexts. For example, ZIPX and EXE are effective in terms of compression rate, while XZ excels in Unix and Linux environments. In the research presented, Bandizip was employed to demonstrate versatility in managing compressed files with a focus on compression efficiency and compression rate. Comparative analysis of compression rates revealed that ZIPX, EXE and XZ are optimal for compressing databases, maximizing size reduction without compromising data integrity. These findings underscore the importance of strategically selecting the compression format to optimize the storage and transmission of large volumes of information, especially in database environments.